Discovering consumer preference and their satisfaction level towards branded and unbranded paints. (24th June 2020) - Gupta, Shivam; Bisaria, Charu; Gupta, Suneel
Consumer preference is the study which involves in depth analysis of the attitude of buyers related with buying. The paint industry of India is bifurcated as the organised and unorganised sector. The units which are large and medium-sized form the organised sector while the small scale units come under the unorganised sector. By and by, development of the paint industry of India can be seen from the increase in requirements of the paints, particularly in urban communities. Paint gives the platform that makes the human life colourful and adds beauty to live a life with peace and tranquillity. This exploration has been directed on 50 respondents of Gomti Nagar in Lucknow City. Questionnaire survey technique has been utilised to lead the exploration. The questionnaire was shaped with the close-ended questions. The principle goal of this paper is to discover the consumer's preference and their satisfaction level while acquiring branded and unbranded paints and to explore the factors that help customers to select paints.